Muslim minority and its challenges in the West - Zul’azmi Yaakob,; Wan Fariza Alyati Wan Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Muslim minority communities in the West encounter numerous challenges that impede their social, economic, and political progress. These challenges can make it difficult for Muslims to participate fully in Western society, causing them to feel excluded and marginalized. This paper presents an analysis of the main factors contributing to intolerant attitudes and discrimination towards Muslim minorities in the West, using content analysis as the methodological approach. The study highlights the significance of negative media portrayals of Muslims, political rhetoric that stigmatizes and marginalizes them, and the double standards in the application of laws and policies as the primary factors contributing to discrimination and exclusion. Addressing these challenges requires a multifaceted approach, including education and awareness-raising campaigns to promote positive narratives about Muslims, interfaith dialogue to increase understanding and tolerance, political engagement to enhance representation and influence in public policy decisions, community building to promote social cohesion, and legal protections to prevent discrimination and hate crimes. Moreover, Muslims as a minority group in the West are expected to promote the beautiful Islamic ethics of Akhlaq in their daily life and participate actively in the broader community.